تأثر الكبد وخلاياه فى الفئران المختبرية بعد الإصابة بالمقوسات الكوندية - رحيمو، زهير إبراهيم فتوحي; الدليمى، لقاء حسين على (جامعة الموصل - كلية التربية الأساسية, 2007)
عزلت القوسات الكوندیة من مشیمات نساء مجهضات وبعد حقن هذه المقوسات داخل خلب هذه الفئران من نوع بالب سي balb/cتم متابعة الكبد وخلایاه بهذه الإصابة وذلك بتشریح الفئران بعد فترات تراوحت ما بین 5-٣٠ یوما بعد الإصابة وأخذت أكبادها للتقطیع النسیجي. بعد ٥ أیام من الإصابة لوحظ تضخم في خلایا كوفر كذلك تم تشخیص حالة التهاب الكبد الحاد المتمثل بأرتشاح الخلایا وحیدة النواة ذات الأنویة متعددة الفصوص. وفي مقاطع أخرى تم تشخیص الأحتقان في الورید الكبدي المركزي فضلا عن تمییز ظاهرة التكیف الوعائي المتمثل بارتشاح الخلایا اللمفیة حول الأقنیة الكبدیة وبالقرب من الورید الكبدي المركزي فضلا عن تمییز ظاهرة التنكز الفجوي في هیولي خلایا الكبد. بعد ١٠ ایام من الإصابة شوهد توسع واحتقا ن في الأوردة المركزیة الكبدیة فضلا عن استمرار تمییز ظاهرة التكفیف الوعائي المتمثل بارتشاح الخلایا اللمفیة حول الأوعیة .كذلك لوحظ التوسع الاحتقان في الورید المركزي بعد ٢٠ یوما بعد الإصابة تم تشخیص الالتهاب المزمن في نسیج الكبد والمتمثل بارتشاح الخلایا وحیدة النواة واللمفیات تحت محفظة الكبد وعند حافة الفصوص الكبدیة فضلا عن النخر الشدید وتضخم خلایا كوفر بعد ٣٠ يوما من الفحص لوحظت الأكیاس النسجیة فضلا عن النخر الشدید في خلایا ونسیج الكبد Toxoplasma gondii specimens were isolated from the placentae of aborted women after injection of these parasites intraperiteonially in balb\c mice, livers and their cells were investigated to report the effect on them and after dissecting out the mice in different periods ranged between 5-30 days after infection as pieces of these liver were taken for histological sectioning. After (5) days of infection enlargement of Kuffer cells were noticed and acute hepatitis of liver was evident represented by infiltration of monocytes which have lobed nuclei. In other sections congestion was diagnosed in the central hepatic vein in addition to distinguishing perivascular cuffing rep [resented by infiltration of lymphocytes surrounding the hepatic vessels near the central hepatic vein in addition of distinguishing vascular degeneration in the cytoplasm of hepatic cells. After (10) days of infection dilatation and congestion in the central hepatic veins and continuous observation of perivascular cuffing represented by infiltration of lymphocytes surrounding vessels in addition to dilatation and congestion of central vein. After(20) after infection chronic hepatitis in liver tissues was noticed represented by infiltration of monocytes and lymphocytes underneath the liver capsule and the margins of liver lobes in addition to sever necrosis and enlargement of Kuffer cells. After (30) days from infection tissue cysts were noticed in addition to sever necrosis in the cells and tissues of the liver.
Keywords: الامراض -- الطب البيطرى -- المقوسات الكوندية -- التجارب العلمية -- الفئران -- التهاب الكبد -- الاوعية الدموية -- الخلايا